Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.7863/jum.2001.20.7.749
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically guided renal mass biopsy: indications and efficacy.

Abstract: For specific clinical indications, sonographically guided fine-needle aspiration and core biopsy of a solid renal mass can be performed safely. In many cases, a definitive diagnosis can be made on the basis of fine-needle aspiration alone. However, diagnosis may ultimately require core biopsy, for which 18-gauge core needles would be more reliably diagnostic than 20-gauge needles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 6 publications
(9 reference statements)
4
34
0
1
Order By: Relevance
“…When feasible, sonography is the guidance method of choice at many institutions for procedures targeting the liver, kidneys, pancreas and lymph nodes (Paulsen et al 2006, Sheafor et al 1998, Won et al 2003, Johnson et al 2001, Tang et al 2002. Advantages of US include widespread availability, real-time operation, relatively low cost and the lack of ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…When feasible, sonography is the guidance method of choice at many institutions for procedures targeting the liver, kidneys, pancreas and lymph nodes (Paulsen et al 2006, Sheafor et al 1998, Won et al 2003, Johnson et al 2001, Tang et al 2002. Advantages of US include widespread availability, real-time operation, relatively low cost and the lack of ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…1 All areas of the body are suitable sites for this procedure including superficial palpable masses or deeply seated lesions or that has been visible only with the use of imaging modalities. FNAC has been widely applied in the diagnosis of tumors and tumor like lesion of the abdomen including the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…FNAC has been widely applied in the diagnosis of tumors and tumor like lesion of the abdomen including the kidney. 1,2 The advantages are a rapid diagnosis, minimal trauma to the patient and low cost when compared with the surgical open biopsy the object of this study is to report our experience about the role of FNAC in the diagnosis of renal masses. [1][2][3] In early studies, pyelography alone determined the puncture site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the data that we used to inform biopsy performance in our model were derived predominantly from studies that reported use of 18-gauge or larger needles or a combination of core biopsy and fi ne needle aspiration ( 14,(26)(27)(28)(29)(31)(32)(33)(34)(35)60 ), but a few studies used fi ne needle aspiration only ( 11,30 ). Practice patterns in using core biopsy and fi ne needle aspiration for renal tumor sampling differ by institution.…”
Section: Health Policy and Practice: Cost-effectiveness Analysis For mentioning
confidence: 99%